العلاقة بين أبعاد الإعلان الهجومي (Guerilla) والاتجاهات نحو العلامة: دراسة تطبيقية على عملاء "المواد الغذائية المصنعة" في مصر - عبدالحميد، طلعت أسعد; دويدار، مصعب أحمد بسيوني (جامعة بنها - كلية التجارة, 2021)
تناول الباحثين في هذه الدراسة تحديد العلاقة بين أبعاد الإعلان الهجومي والاتجاهات نحو العلامة، وذلك بالتطبيق على عملاء المواد الغذائية المصنعة في مصر. ولتجميع البيانات تم تصميم قائمة الاستقصاء وقام الباحثين باستخدام الاستقصاء عبر الإنترنت، وإتاحته لجمهور واسع من المشاركين المحتملين، وتم توجيهها إلى عملاء "المواد الغذائية المصنعة" في مصر وتحديدا بين الفترة من 19 /12 /2020م حتى 31 /1 /2021م. ولتحليل البيانات الأولية للدراسة، تم استخدام البرنامج الإحصائي SPSS v26 لإدخال البيانات الأولية وتحليل فروض الدراسة، وقد بلغ حجم العينة المختارة ٣٨٤ مفردة. وقد أوضحت نتائج التحليل الإحصائي وجود علاقة ارتباط (متوسطة القوى) ذات دلالة إحصائية بين أبعاد الدراسة (الحداثة، الملاءمة، الجماليات، الدعابة، الوضوح، المفاجأة، الاستثارة العاطفية، والاتجاهات نحو العلامة) عبر عملاء المواد الغذائية المصنعة محل الدراسة، حيث جاءت دالة إحصائيا عند مستوى دلالة (0.01)، كما توصلت نتائج الدراسة الحالية أنه يوجد تأثير معنوي لأبعاد الإعلان الهجومي (الاستثارة العاطفية، والملاءمة، والوضوح) على اتجاهات عملاء المواد الغذائية المصنعة في مصر نحو العلامة، وعدم وجود تأثير ذو أهمية لكل من (الحداثة، والجماليات، والدعابة، والمفاجأة) على اتجاهات العملاء نحو العلامة. In this study, the Researchers addressed the relationship of the dimensions of Guerrilla advertising to Attitude towards the brand, by applying to customers of food manufactured in Egypt. For collecting the data, the survey list was designed, and the Researchers used the online survey, made available to a wide audience of potential participants, and was directed to customers of "processed food" in Egypt, specifically from 19/12/2020 until 31/1/2021. To analyze the primary data of the study, the SPSS V26 statistical program was used to enter the primary data and analyze the study hypotheses, with a sample size of 384 individuals. The results of the statistical analysis showed a statistically significant correlation (Medium-strength) between the dimensions of the study (Novelty, Relevance, aesthetics, humor, clarity, surprise, emotional arousal) through on Attitude towards the brand of foodstuffs manufactured in Egypt under study, Where a function came statistically at the level of indication (0.01), as the results of the current study found that there is a moral effect of the dimensions of guerrilla advertising (Emotional Arousal, Clarity, Relevance) on the Attitude towards the brand, and there is no effect important of (Novelty, aesthetics, humor, surprise) on Attitude towards the brand.
Keywords: صناعة الأغذية -- النشاط الإعلاني -- الشبكة العنكبوتية -- اتجاهات العملاء -- مصر